2015
DOI: 10.1161/str.46.suppl_1.wp98
|View full text |Cite
|
Sign up to set email alerts
|

Abstract W P98: Monocyte Chemotactic Protein-3 Elevated in Stoke and Aging

Abstract: Background: It is now recognized that stroke is a systemic stressor that triggers profound changes throughout the body, leading to alterations in the immune system and response. In the CNS, cell death from ischemic stroke activates glial cells, leading to trafficking of leukocytes into the brain and subsequent inflammation. Chemokines play an active role in modulating this recruitment process. Monocyte chemotactic protein-3 (MCP-3), also known as CCL7, is a chemokine that attracts a broad spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Most current studies focus on the effect of chemokines on stroke rather than ischemic stroke. Early animal experiments suggested elevated MCP3 was associated with stroke, especially in aging mice ( Townshend et al, 2015 ). Extensive research using animal models has shown a vital role for monocyte chemotactic protein-1 (MCP1) in atherogenesis and atheroprogression ( Aiello et al, 1999 ; Inoue et al, 2002 ; Lin et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most current studies focus on the effect of chemokines on stroke rather than ischemic stroke. Early animal experiments suggested elevated MCP3 was associated with stroke, especially in aging mice ( Townshend et al, 2015 ). Extensive research using animal models has shown a vital role for monocyte chemotactic protein-1 (MCP1) in atherogenesis and atheroprogression ( Aiello et al, 1999 ; Inoue et al, 2002 ; Lin et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%